Surgical treatment of T2-3 posterior hypopharyngeal carcinoma with preservation of laryngeal function. (1st September 2021) - Chen, Ling; Si, Yu; Lin, Peiliang; Guan, Zhong; Zhu, Wenying; Liang, Haifeng; Cai, Qian
Abstract: Background: Posterior hypopharyngeal carcinoma indicates a poor prognosis. Previous treatments predicted negative influence to the pronunciation and swallowing function. The present study focuses on improving survival rate while improving quality of life. Aim: To investigate on the surgical techniques of the preservation of laryngeal function of posterior hypopharyngeal carcinoma. Methods: Eighteen patients with posterior hypopharyngeal carcinoma of T2-T3 were studied. All primary lesions were removed and the defects were repaired with the radial forearm free flap (RFFF). Results: The 3-year overall survival rate was 51.9%. All patients could maintain daily caloric intake by feeding orally, and remove the gastric tube 28–61 days after operation. Assessed swallowing function by Fiberoptic endoscopic evaluations of swallowing. When eating solid food, 66.67% patients had food residue; no food entered airway, and all patients had Penetration-Aspiration Scale of level 1. As for liquid, 11.11% patients had level 5, 16.67% level 4, 27.78% level 2 and 44.44% level 1. Conclusions: By preserving the integrity of larynx and superior laryngeal nerve with repairing the defects of posterior wall of hypopharynx with RFFF, patients with T2 and T3 stage posterior hypopharyngeal carcinoma could live a better quality of life.